Analysis of Generation Z's Perspective at Pondok Putri Roudhotul Qur'an An-Noer in Learning Religion Through the Media "Instagram" - Aufia Aisa; Mirza Zamrotul Ilma Sari (SCHOOLAR: Social and Literature Study in Education, 2021)
In this study, it is explained that generation Z is a generation that was born during the rapid development of social media, causing generation Z to be different from the previous generation, starting from personality, psychology and distinctive characters that are different from previous generations who do not have a post-modern environment setting. Social media or social media is an online media that is easy to share knowledge and others. Instagram is often used as a medium of da'wah by preachers, because social media Instagram is a social media that is very loved by people today, especially from the youth group. In addition, Instagram social media users can also be done anytime and anywhere, besides that we can exchange opinions, knowledge because religious learning is very important to strengthen identity and act in doing something. But we must remain careful in accepting because now many spread religious learning that was not accepted by the original sources and the sources were clear. Here there are positive and negative sides, from the positive side, it can be said that it is cool because Instagram is part of today's technological sophistication which is much loved by young people, meaning that if preaching, broadcasting religious teachings, it is easier for young people to follow who may not be able to attend. at the recitation ceremony directly. The negative factor is that not everyone has an Instagram application, so if religious learning through Instagram media will be less comprehensive.